1995
DOI: 10.1002/etc.5620141120
|View full text |Cite
|
Sign up to set email alerts
|

ΣPAH: A Model to predict the toxicity of polynuclear aromatic hydrocarbon mixtures in field‐collected sediments

Abstract: The ΣPAH model estimates the probability of toxicity of PAH‐contaminated sediments using a combination of equilibrium partitioning, QSAR, toxic unit, additivity, and concentration‐response models. The sediment concentration of organic carbon and 13 PAH (polynuclear aromatic hydrocarbon) compounds were measured. Interstitial water concentrations (PAH1W) of the 13 compounds were predicted by equilibrium partitioning. The 10‐d LC50 of each compound in interstitial water (10‐d LC501W) was predicted by a QSAR regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
112
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(118 citation statements)
references
References 25 publications
5
112
0
1
Order By: Relevance
“…As shown in Fig. 2 (Swartz et al 1995). This may be attributed to subtle differences in exposure levels and aquatic ecosystem structure and functions in different study areas, as well as regional water quality parameters such as pH, dissolved organic matter (DOM), and hardness.…”
Section: Probabilistic Distributions Of Hazard Quotientsmentioning
confidence: 99%
“…As shown in Fig. 2 (Swartz et al 1995). This may be attributed to subtle differences in exposure levels and aquatic ecosystem structure and functions in different study areas, as well as regional water quality parameters such as pH, dissolved organic matter (DOM), and hardness.…”
Section: Probabilistic Distributions Of Hazard Quotientsmentioning
confidence: 99%
“…1,[42][43][44][45][46][47][48] At the same time, there is also considerable controversy over the effectiveness of these sediment guidelines in assessing ecological risks caused by PAHs. 49,50 However, Swartz 51 has noted that these sediment quality guidelines are more similar than dissimilar, and has proposed consensus guidelines for PAHs, i.e., threshold, median and extreme effects concentration (TEC, MEC and EEC).…”
Section: Ecological Risk Assessmentmentioning
confidence: 99%
“…Values for log LC were available from Swartz et al (1995) and are summarized in Table 10. PAHsCdiment and foc values were available for the three samples from chemical analyses conducted as part of the SQT.…”
Section: Predicted Pah Porewater Concentrationsmentioning
confidence: 99%
“…These physical sediment characteristics also influence the bioavailability of COPCs, and make predictions of adverse biological effects based on bulk sediment concentrations unreliable. As a result, equilibrium partitioning models and toxicity testing based on porewater exposures have been used for derive sediment quality criteria for metals (Ankley et al, 1996), nonionic organic compounds (Di Toro et al, 1991), PAHs (Di Toro and McGrath, 2000) and PAH mixtures (Swartz et al, 1995) based on observed correlations between porewater concentrations and adverse biological effects in different benthic organisms. The SQGs are estimated from an acceptable porewater concentration and mathematical formula intended to represent the relationship between porewater and bulk sediment COPC concentrations.…”
Section: Consideration Of Multiple Copc Exposure Pathwaysmentioning
confidence: 99%